ANALISIS PERLAKUAN AKUNTANSI ASET TETAP BERDASARKAN SAK-ETAP NO. 15 PADA KOPERASI PT. PISMA PUTRA TEXTILE PEKALONGAN - Ariyanti, Rizka; Murniati, Sri (BAPPEDA Kota Pekalongan, 2019)
Assets still have sufficient material value in the financial statements and are an important part in supporting cooperative operations. Therefore cooperatives need to implement fixed asset accounting policies in accordance with the Entity Financial Accounting Standards without Public Accountability (SAK-ETAP) No.15. This study aims to obtain empirical evidence and analyze the accounting treatment of fixed assets applied to the co operatives of PT. Pisma Putra Textile. The research method used is descriptive method with a qualitative approach and data collection techniques by means of field studies and literature. The types of data used in the study are primary data and secondary da ta. After an analysis of the results of interviews and searches for documents related to the classification of fixed assets, the recognition and presentation of assets can still be known that the cooperative PT. Pisma Putra Textile has not applied the treatment of its fixed assets in accordance with the Entity Financial Accounting Standards without Public Accountability (SAK-ETAP) No.15. Keywords: Classification of fixed assets, Recognition, Presentation, SAK-ETAP No.15.